Haulout patterns of grey seals Halichoerus grypus in the Baltic Sea - Sjoberg, M; McConnell, B; Fedak, M (1999)
The haulout pattern of seals, i.e. the distribution of the time they spend on shore or on ice, may be influenced by a large number of extrinsic factors such as season, time of day and weather, as well as factors related to the animal's internal state. In this study we used a time-lapse video system at a haulout site, and satellite relay data loggers attached to 11 individual seals to monitor haulout pattern of grey seals Halichoerus grypus in the Baltic Sea during summer and early winter from 1989 through 1996. Time of day had the greatest influence on haulout patterns with the maximum numbers of seals ashore at night. Season and habitat specific characteristics also had important effects on haulout pattern. We suggest that diel changes in prey behaviour and distribution account for the nocturnal haulout pattern observed. The size of the population of grey seals in the Baltic Sea has been estimated by the number of seals ashore. Our results demonstrate the possibility of improving future estimates using a correction based on time of day.